ANALYSIS OF JUDICIAL CONSIDERATIONS IN IMPOSING SEVERE SENTENCES ON NARCOTICS DEALERS IN THE DECISION OF THE MEDAN DISTRICT COURT NUMBER 1219/PID.SUS/2025/PN MDN - Supongki Adi Sucipto; Tri Reni Novita (CV. Barokah Publsiher, 2026)
Based on the results of the study, it shows that the legal regulations regarding the crime of selling narcotics based on Law Number 35 of 2009 concerning Narcotics have been regulated in Articles 114, 119 and 124. The differences between Articles 114, 119, and 124 are not only in the different types of narcotics, but also in the varying criminal sanctions. The conformity of the principles of criminal justice and the purpose of punishment with the decision of the heavy sentence imposed by the judge in the Medan District Court Decision 1219 / Pid.Sus / 2025 / PN Mdn is appropriate, namely the heavy sentence determined by the judge has fulfilled the principle of legality, the principle of equality before the law, and the principle of proportionality. The judge's consideration in imposing a heavy sentence on the perpetrator of narcotics sales in the Medan District Court Decision 1219 / Pid.Sus / 2025 / PN Mdn is appropriate because the 9-year prison sentence has fulfilled the principle of proportional justice.